Can Bath Ankylosing Spondylitis Disease Activity Index be Affected by Accompanying Fibromyalgia or Depression? - Lale ALTAN,; Yusuf SİVRİOĞLU,; İlker ERCAN, (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate whether Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) is affected from pathologies such as fibromyalgia (FM) and depression which may coexist in patients with ankylosing spondylitis (AS). Patients and methods: A total of 170 patients (57 males, 123 females; mean age 42.9±13.0 years) aged between 18 and 75 years with FM (n=52), depression (n=60) and AS (n=58) were included in the study. All patients were asked to complete BASDAI and Beck Depression Inventory. Percentages of patients with BASDAI scores of >4 (cut-off value for disease activity) and >5 (cut-off value for reimbursement of biological agents) were calculated and compared between the groups. Individual BASDAI item scores, total BASDAI, and Beck Depression Inventory scores were compared between the groups. Results: When individual BASDAI items scores were analyzed separately, scores of all items were statistically significantly higher in FM group compared to AS group. While question 1 (fatigue) and 3 (peripheral joint pain and swelling) scores were statistically significantly higher in the depression group compared to AS group, question 5 and 6 scores (items associated with morning stiffness) were significantly lower in the depression group compared to AS group. Percentage of patients with BASDAI scores of >4 and >5 in the FM group was significantly higher compared to the other two groups. Significant correlation was noted between BASDAI and Beck Depression Inventory scores in AS and FM groups. Conclusion: Our findings suggest that while assessing disease activity in patients with AS particularly by a patient-reported outcome measure such as BASDAI, other conditions such as FM and depression which may affect the scores should be taken into consideration.